On-line fault detection and end-of-batch quality prediction for batch processes incorporating on-line synchronisation and phase identification - Myburgh, Travis Louis (Stellenbosch : Stellenbosch University, 2016)
Thesis (MEng)--Stelllenbosch University, 2016.